Poly-3-hydroxyalkanoates-co-polyethylene Glycol Methacrylate Copolymers for pH Responsive and Shape Memory Hydrogel - Gumel, A.M.; Annuar, M.S.M. (Wiley, 2014)
Multifunctional hydrogels combining the capabilities of cellular pH responsiveness and shape memory, are highly promising for the realization of smart membrane filters, controlled drug released devices, and functional tissue-engineering scaffolds. In this study, lipase was used to catalyze the synthesis of medium-chain-length poly-3-hydroxyalkanoates-co-polyethylene glycol methacrylate (PHA-PEGMA) macromer, which was used to prepare pH-responsive and shape memory hydrogel via free radical polymerization. Increasing the PEGMA fraction from 10 to 50% (mass) resulted in increased thermal degradation temperature (T-d) from 430 to 470 degrees C. Highest lower critical solution temperature of 37 degrees C was obtained in hydrogel with 50% PEGMA fraction. The change in PEGMA fraction was also found to highly influence the hydrogel's hydration rate (r) from 2.8 x 10(-5) to 7.6 x 10(-5) mL.s(-1). The hydrogel's equilibrium weight swelling ratio (q(e)), protein release and its diffusion coefficient (D-m) were all found to be pH dependent. Increasing the phosphate buffer pH from 2.4 to 13 resulted in increased q(e) from 2 to 16 corresponding to the enlarging of network pore size (xi) from 150 to 586 nm. Different types of crosslinker for the hydrogel influenced its flexibility and ductility. (C) 2014 Wiley Periodicals, Inc.